Effectiveness of the Program to Encourage Active, Rewarding Lives (PEARLS) to reduce depression: a multi-state evaluation - Smith, Matthew Lee; Steinman, Lesley E.; Montoya, Carol N.; Thompson, Meghan; Zhong, Lixian; Merianos, Ashley L. (Frontiers in Public Health, 2023)
Introduction An estimated 15% of community-dwelling older adults have depressive symptoms in the U.S. The Program to Encourage Active, Rewarding Lives (PEARLS) is an evidence-based program for managing late-life depression. PEARLS is a home/community-based collaborative care model delivered by community-based organizations to improve access to quality depression care. Trained staff actively screen for depression to improve recognition, teach problem-solving and activity planning skills for self-management, and connect participants to other supports and services as needed. Methods This study examined 2015–2021 data from 1,155 PEARLS participants across four states to assess PEARLS effectiveness to reduce depressive symptoms. The clinical outcomes were measured by the self-reported PHQ-9 instrument to assess changes in depressive symptoms scored as depression-related severity, clinical remission, and clinical response. A generalized estimating equation (GEE) model was fitted to examine changes in composite PHQ-9 scores from baseline to the final session. The model adjusted for participants’ age, gender, race/ethnicity, education level, income level, marital status, number of chronic conditions, and number of PEARLS sessions attended. Cox proportional hazards regression models were conducted to estimate the hazard ratio for improvement of depressive symptoms (i.e., remission or response), while adjusting for the covariates. Results PHQ-9 scale scores significantly improved from baseline to their final sessions (mean difference = −5.67, SEM = 0.16, p < 0.001). About 35% of participants achieved remission with PHQ-9 score < 5. Compared to participants with mild depression, patients with moderate depression (HR = 0.43, 95%CI = 0.35–0.55), moderately severe depression (HR = 0.28, 95%CI = 0.21–0.38), and severe depression (HR = 0.22 95%CI = 0.14–0.34) were less likely to experience clinical remission with PHQ-9 score < 5, while adjusting for the covariates. About 73% achieved remission based on no longer having one or both cardinal symptoms. Compared to participants with mild depression, patients with moderate depression (HR = 0.66, 95%CI = 0.56–0.78), moderately severe depression (HR = 0.46, 95%CI = 0.38–0.56), and severe depression (HR = 0.38, 95%CI = 0.29–0.51) were less likely to experience clinical remission, while adjusting for the covariates. Nearly 49% of participants had a clinical response or a ≥ 50% decrease in PHQ-9 scores over time. There were no differences between the severity of depression groups based on the time to clinical response. Discussion Findings confirm that PEARLS is an effective program to improve depressive symptoms among older adults in diverse real-world community settings and can be a more accessible option for depressive older adults who are traditionally underserved by clinical care.